Lower hybrid waves at ionospheric heights - Misra K.D.; Gwal A.K. (My University, 2025)
Growth of electrostatic waves around the lower hybrid resonance (LHR) frequency has been discussed. Expressions for growth rate of the excited electrostatic wave around the LHR frequency have been derived and evaluated for ionospheric plasma parameters. The results are in good agreement with the experimental observations reported by earlier workers.